COFFEE LOWERS BLOOD GLUCOSE LEVELS BUT FAILS TO IMPROVE SKELETAL MUSCLE MASS IN ALLOXAN-INDUCED RATS - AISYAH, RIANDINI; JATMIKO, SAFARI WAHYU; MAHMUDAH, NUR (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to evaluate the potency of coffee as a non-pharmacological alternative treatment for diabetes melitus by measuring blood glucose levels, skeletal muscle diameter, and the number of skeletal muscle cell nuclei. Methods: This study used 24 Rattus norvegicus weighing 150-250g and divided them into 6 groups: non-diabetic control, diabetic control, insulin, Lampung Robusta coffee at doses of 0.054g/200g b. w, 0.108 g/200g b. w, 0.162g/200g b. w, respectively. Rats were acclimatized for 7 days before the treatment. All groups except the non-diabetic control were injected with alloxan at a dose of 125 mg/kg b. w. Coffee was made by dissolving each dose with hot water without using any sweeteners. Coffee was administered for 14 d, and blood sugar levels were measured before and after the treatment. The gastrocnemius muscle was taken for histopathological test to measure the diameter and quantify the number of cell nuclei. The data was analyzed with the One-Way Anova for body weight and muscle diameter and Kruskal-Wallis tests performed to analyze blood glucose and myonuclear number. Results: Kruskal-Wallis test showed the significance of blood sugar levels p=0.01, Dunn’s Post Hoc comparisons of animal group test showed significant differences between groups 1-3, 2-3, and 4-6. Body weight, muscle diameter, and muscle cell nuclei number exhibited no significant differences within the groups. The Spearman's rho test indicated no significant correlation between muscle diameter and myonuclear number (0.474). Conclusion: On the 14th day of treatment, coffee was able to lower blood sugar levels but was unable to improve skeletal muscle diameter as well as myonuclear number.